Population level effects of the active kids program on children and adolescents’ physical activity and sport participation in NSW, Australia - Katherine B. Owen; Bridget C. Foley; Lindsey J. Reece; William Bellew; Adrian Bauman (International Journal of Behavioral Nutrition and Physical Activity)
Abstract Background Active Kids was a universal program that aimed to reduce the cost of sport and active recreation programs for all school-enrolled children and adolescents (4.5–18 years) in New South Wales (NSW), Australia through provision of $100 vouchers. This study assesses trends in physical activity and sport participation in children and adolescents in NSW during its implementation to determine population level program effects. Methods This study used the Active Kids program data from January 31 2018 to December 31 2022. Children and adolescents who registered in the program provided physical activity and sport participation data each year. The NSW Population Health Survey (PHS) and NSW AusPlay data measured the same outcomes from 2017 to 2022 in representative samples of the population. We calculated weighted prevalence estimates for physical activity and sport participation each year, and by age, gender, and socioeconomic status. Results In the five-years of Active Kids program implementation, there was a slight decrease in the proportion of children and adolescents meeting physical activity guidelines (2018: 19.3%, 95% CI 19.2–19.4; 2022: 16.1%, 95% CI 16.0-16.2). In PHS between 2017 and 2022, there was also a slight decrease in the proportion of children and adolescents meeting physical activity guidelines (2017: 32.6%, 95% CI 29.1–36.0; 2022: 27.9%, 95% CI 24.4–31.5), with a larger drop in 2020 (24.4%, 95% CI 20.8–27.9). In the same period (2018–2022), there was a decrease in the proportion of children and adolescents who participated in sport at least once per week (2018: 70.3%, 95% CI 70.2–70.4; 2022: 53.6%, 95% CI 53.5–53.7). There was also a decrease in the proportion of children and adolescents who participated in sport at least once per week between 2017 and 2021 (2017: 78.2% 95% CI 74.5–81.9; 2021: 63.4%, 95% CI 60.1–66.8), with a slight increase in 2022 (69.8%, 95% CI 66.7–72.9). Conclusions We found no increases in overall population levels of physical activity or sport participation among children and adolescents in NSW between 2017 and 2022. The single-component, universal program design should be modified, using targeted behaviour change theories, to address inequalities and stimulate population-level increases in physical activity and sport participation. Trial registration Australian New Zealand Clinical Trials Registry (ACTRN12618000897268).